2009
DOI: 10.1007/s00894-009-0492-3
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical modeling and experimental studies on N-n-Decyl-2-oxo-5-nitro-1-benzylidene-methylamine

Abstract: The Schiff base compound, N-n-Decyl-2-oxo-5-nitro-1-benzylidene-methylamine, has been -synthesized and characterized by IR, electronic spectroscopy, and X-ray single-crystal determination. Molecular geometry from X-ray experiment of the title compound in the ground state have been compared using the Hartree-Fock (HF) and density functional method (B3LYP) with 6-31G(d) basis set. Calculated results show that density functional theory (DFT) at B3LYP/6-31G(d) level can well reproduce the structure of the title co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Literature survey revealed that the DFT has a great accuracy in reproducing the experimental values of geometry, vibrational frequency, electronic absorption spectra, etc. [16,17].…”
Section: Inroductionmentioning
confidence: 99%
“…Literature survey revealed that the DFT has a great accuracy in reproducing the experimental values of geometry, vibrational frequency, electronic absorption spectra, etc. [16,17].…”
Section: Inroductionmentioning
confidence: 99%
“…[15][16][17][18][19] In this paper, we report the synthesis, characterization and crystal structure of the compound 3-(2-Mercaptopyridine)phthalonitrile as well as the theoretical studies on it by using the HF/6-31G(d) and DFT/B3LYP/6-31G(d) methods. The properties of the structural geometry, molecular electrostatic potential (MEP), thermodynamic properties and nonlinear optical properties for the title compound at the B3LYP/6-31G(d) level were studied.…”
Section: Introductionmentioning
confidence: 99%
“…Many imperative chemicals and physical properties of biological systems can be predicted by various computational techniques [38,39]. In recent years, density functional theory (DFT) with a better exchange-correlation functional has made it possible to calculate many molecular properties with comparable accuracies to traditional correlated ab initio methods [40]. Literature survey also reveals that the DFT has a greater accuracy in reproducing the experimental results [41][42][43][44][45].…”
Section: Page 5 Of 39mentioning
confidence: 99%